Chemical bath deposition of textured and compact zinc oxide thin films on vinyl-terminated polystyrene brushes - Blumenstein, Nina J.; Hofmeister, Caroline G.; Lindemann, Peter; Huang, Cheng; Baier, Johannes; Leineweber, Andreas; Walheim, Stefan; Wöll, Christof; Schimmel, Thomas; Bill, Joachim (Beilstein Journal of Nanotechnology, 2016)
In this study we investigated the influence of an organic polystyrene brush on the deposition of ZnO thin films under moderate conditions. On a non-modified SiOx surface, island growth is observed, whereas the polymer brush induces homogeneous film growth. A chemical modification of the polystyrene brushes during the mineralization process occurs, which enables stronger interaction between the then polar template and polar ZnO crystallites in solution. This may lead to oriented attachment of the crystallites so that the observed (002) texture arises. Characterization of the templates and the resulting ZnO films were performed with ζ-potential and contact angle measurements as well as scanning electron microscopy (SEM), atomic force microscopy (AFM) and X-ray diffraction (XRD). Infrared spectroscopy (IR) measurements were used to investigate the polystyrene brushes before and after modification.
Keywords: bioinspired synthesis; polymer brush; template activation; thin film growth; zinc oxide

(untitled) - Pearton, S. J.; Norton, D. P.; Ip, K.; Heo, Y. W.; Steiner, T. (Prog. Mater. Sci., 2005)

Zinc Oxide: From Fundamental Properties Towards Novel Applications - Klingshirn, C. F.; Meyer, B. K.; Waag, A.; Hoffmann, A.; Geurts, J. (Springer, 2010)

(untitled) - Wei, A.; Pan, L.; Huang, W. (Mater. Sci. Eng., B, 2011)

(untitled) - Wang, Z. L. (MRS Bull., 2012)

(untitled) - Chen, Y.-C.; Goering, E.; Jeurgens, L.; Wang, Z.; Phillipp, F.; Baier, J.; Tietze, T.; Schütz, G. (Appl. Phys. Lett., 2013)

(untitled) - Yang, Q.; Liu, Y.; Pan, C.; Chen, J.; Wen, X.; Wang, Z. L. (Nano Lett., 2013)

(untitled) - Pillai, S. C.; Kelly, J. M.; Ramesh, R.; McCormack, D. E. (J. Mater. Chem. C, 2013)

(untitled) - Oprea, O.; Andronescu, E.; Ficai, D.; Ficai, A.; Oktar, F. N.; Yetmez, M. (Curr. Org. Chem., 2014)

(untitled) - Wang, X.; Schröder, H. C.; Müller, W. E. G. (Beilstein J. Nanotechnol., 2014)

(untitled) - Preiss, L. C.; Landfester, K.; Muñoz-Espí, R. (Beilstein J. Nanotechnol., 2014)

(untitled) - Abacilar, M.; Daus, F.; Geyer, A. (Beilstein J. Nanotechnol., 2015)

(untitled) - Siglreitmeier, M.; Wu, B.; Kollmann, T.; Neubauer, M.; Nagy, G.; Schwahn, D.; Pipich, V.; Faivre, D.; Zahn, D.; Fery, A.; Cölfen, H. (Beilstein J. Nanotechnol., 2015)

(untitled) - Waltz, F.; Schwarz, H.-C.; Schneider, A. M.; Eiden, S.; Behrens, P. (Beilstein J. Nanotechnol., 2015)

(untitled) - Chen, C.-L.; Rosi, N. L. (Angew. Chem., Int. Ed., 2010)

(untitled) - Togashi, T.; Yokoo, N.; Umetsu, M.; Ohara, S.; Naka, T.; Takami, S.; Abe, H.; Kumagai, I.; Adschiri, T. (J. Biosci. Bioeng., 2011)

(untitled) - Liang, M.-K.; Deschaume, O.; Patwardhan, S. V.; Perry, C. C. (J. Mater. Chem., 2011)

(untitled) - Waltz, F.; Wißmann, G.; Lippke, J.; Schneider, A. M.; Schwarz, H.-C.; Feldhoff, A.; Eiden, S.; Behrens, P. (Cryst. Growth Des., 2012)

(untitled) - Altintoprak, K.; Seidenstücker, A.; Welle, A.; Eiben, S.; Atanasova, P.; Stitz, N.; Plettl, A.; Bill, J.; Gliemann, H.; Jeske, H.; Rothenstein, D.; Geiger, F.; et al. (Beilstein J. Nanotechnol., 2015)

(untitled) - Sanctis, S.; Hoffmann, R. C.; Eiben, S.; Schneider, J. J. (Beilstein J. Nanotechnol., 2015)

(untitled) - Baier, J.; Strumberger, R.; Berger, F.; Atanasova, P.; Welzel, U.; Bill, J. (Biointerface Res. Appl. Chem., 2012)

(untitled) - Baier, J.; Naumburg, T.; Blumenstein, N. J.; Jeurgens, L. P. H.; Welzel, U.; Do, T. A.; Pleiss, J.; Bill, J. (Biointerface Res. Appl. Chem., 2012)

(untitled) - Baier, J.; Blumenstein, N. J.; Preusker, J.; Jeurgens, L. P. H.; Welzel, U.; Do, T. A.; Pleiss, J.; Bill, J. (CrystEngComm, 2014)

(untitled) - Blumenstein, N. J.; Berson, J.; Walheim, S.; Atanasova, P.; Baier, J.; Bill, J.; Schimmel, T. (Beilstein J. Nanotechnol., 2015)

(untitled) - Bae, S. Y.; Na, C. W.; Kang, J. H.; Park, J. (J. Phys. Chem. B, 2005)

(untitled) - Babar, A. R.; Deshamukh, P. R.; Deokate, R. J.; Haranath, D.; Bhosale, C. H.; Rajpure, K. Y. (J. Phys. D: Appl. Phys., 2008)

(untitled) - Huang, Y.-C.; Li, Z.-Y.; Chen, H.-H.; Uen, W.-Y.; Lan, S.-M.; Liao, S.-M.; Huang, Y.-H.; Ku, C.-T.; Chen, M.-C.; Yang, T.-N.; Chiang, C.-C. (Thin Solid Films, 2009)

(untitled) - Chen, K. J.; Hung, F. Y.; Chang, S. J.; Hu, Z. S. (Appl. Surf. Sci., 2009)

(untitled) - Janotti, A.; de Walle, C. G. V. (Rep. Prog. Phys., 2009)

(untitled) - Sans, J. A.; Sánchez-Royo, J. F.; Segura, A.; Tobias, G.; Canadell, E. (Phys. Rev. B, 2009)

(untitled) - Zhao, J.; Yan, X.; Yang, Y.; Huang, Y.; Zhang, Y. (Mater. Lett., 2010)

(untitled) - Shinde, V. R.; Lokhande, C. D.; Mane, R. S.; Han, S.-H. (Appl. Surf. Sci., 2005)

(untitled) - Nafees, M.; Liaqut, W.; Ali, S.; Shafique, M. A. (Appl. Nanosci., 2013)

(untitled) - Eisele, R.; Blumenstein, N. J.; Baier, J.; Walheim, S.; Schimmel, T.; Bill, J. (CrystEngComm, 2014)

(untitled) - Lipowsky, P.; Hoffmann, R. C.; Welzel, U.; Bill, J.; Aldinger, F. (Adv. Funct. Mater., 2007)

(untitled) - Lipowsky, P.; Hedin, N.; Bill, J.; Hoffmann, R. C.; Ahniyaz, A.; Aldinger, F.; Bergström, L. (J. Phys. Chem. C, 2008)

(untitled) - Lipowsky, P.; Burghard, Z.; Jeurgens, L. P. H.; Bill, J.; Aldinger, F. (Nanotechnology, 2007)

(untitled) - Maas, J. H.; Cohen Stuart, M. A.; Sieval, A. B.; Zuilhof, H.; Sudhölter, E. J. R. (Thin Solid Films, 2003)

(untitled) - Kosmulski, M.; Matijević, E. (Langmuir, 1992)

(untitled) - Liang, C. Y.; Krimm, S. (J. Polym. Sci., 1958)

Infrared and Raman Characteristic Group Frequencies – Tables and Charts - Socrates, G. (John Wiley & Sons Ltd., 2001)

(untitled) - Kim, S.-W.; Fujita, S.; Fujita, S. (Jpn. J. Appl. Phys., 2002)

(untitled) - Turgeman, R.; Gershevitz, O.; Palchik, O.; Deutsch, M.; Ocko, B. M.; Gedanken, A.; Sukenik, C. N. (Cryst. Growth Des., 2004)

(untitled) - Turgeman, R.; Gershevitz, O.; Deutsch, M.; Ocko, B. M.; Gedanken, A.; Sukenik, C. N. (Chem. Mater., 2005)

(untitled) - Sherman, R.; Hirt, D.; Vane, R. (J. Vac. Sci. Technol., A, 1994)

TOPAS : General Profile. Structure Analysis Software for Powder Diffraction Data. V2.0 - Coelho, A. A. (Bruker AXS GmbH, 2003)

(untitled) - Zawisza, I.; Wittstock, G.; Boukherroub, R.; Szunerits, S. (Langmuir, 2007)